2021
DOI: 10.32350/uer.41.04
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Teacher Competency: Knowledge, Skills, and Aptitude of Secondary School Teachers of Islamabad, Pakistan

Abstract: Teacher competency is the key to effective and quality teaching. According to the Oxford English Dictionary, competency denotes the ability, skill, and strength of an individual used to perform a given task. In order to ascertain the efficacy of the learning outcomes of any education system, teacher competency is measured using knowledge, skills, and attitude (KSA) model. The current study used the same model to assess teacher competency of the secondary school teachers of Islamabad. Stratified random sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…The findings in this study revealed no significant difference There is no significant difference in special education teachers' self-efficacy in the use of Assistive technologies for instruction based on qualification. This finding does not conform with the findings of Parveen et al (2021), whose study affirmed that special education teachers' qualification towards the use of Assistive technology has been the paramount barrier for the effective usage and implementation of Assistive Technology.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The findings in this study revealed no significant difference There is no significant difference in special education teachers' self-efficacy in the use of Assistive technologies for instruction based on qualification. This finding does not conform with the findings of Parveen et al (2021), whose study affirmed that special education teachers' qualification towards the use of Assistive technology has been the paramount barrier for the effective usage and implementation of Assistive Technology.…”
Section: Discussioncontrasting
confidence: 81%
“…Therefore, to handle this concern, the grant money will need to be allocated for setting up a resource centre, hiring technical professionals, and training instructor on how to employ Assistive Technologies within their instructions and methods of teaching students with disabilities. The technology resource centre would be a space within the school where the teacher could find information, software, hardware, and other Assistive Technologies for teaching/learning purposes (Parveen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Such reflective practices are crucial for navigating the complexities inherent in the educational landscape, enabling educators to swiftly adapt to changing classroom dynamics. Furthermore, this reflective approach empowers teachers to tailor their instructional strategies to better address the diverse needs of students, thereby cultivating an enriched and adaptive learning environment (Parveen et al, 2021).…”
Section: Theoretical Framework the Relevance Of Complex Thinking In V...mentioning
confidence: 99%
“…In the 21st century, teacher competence encompasses a wide range of attributes, including expertise in the subject matter, effective teaching skills, positive attitudes, aptitudes, talents, and abilities. Essentially, the caliber of a nation's education system is a substantial indicator of its value (Parveen, Nazir, & Zamir, 2021). Passi (2009) assert that teaching competency refers to a teacher's effective demonstration of conduct that leads to desired outcomes in students.…”
mentioning
confidence: 99%